Hubungan asupan protein hewani, IMT/U, dan waktu tidur dengan kadar hemoglobin pada remaja putri di SMA - Rahmawati, Manda Ayu; Puteri, Hidayatusy Syukrina; Astuti, Dewi Woro; Hervidea, Radella (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Anemia is a common nutritional problem in adolescent girls, especially during periods of rapid growth. One of the main factors causing anemia is low intake of animal protein, which contains heme iron and plays a vital role in hemoglobin formation. Adolescent girls have higher iron requirements, putting them at higher risk of anemia if their diets are inadequate. Purpose: To determine the relationship between animal protein intake, BMI/Age, sleep time, and hemoglobin levels in high school adolescent girls. Method: This study used a quantitative approach with a cross-sectional design. The subjects were 87 tenth- and eleventh-grade adolescent girls selected using a total sampling technique. Data on animal protein intake were collected using a semi-quantitative Fast Response Questionnaire (FFQ), and hemoglobin levels were measured using a digital hemoglobin meter. Data were analyzed using the Spearman Rank test with a significance level of 0.05. Results: The majority of respondents (91.9%) had insufficient animal protein intake. 30.2% of respondents had mild anemia, and 4.7% had moderate anemia. Statistical test results showed a significant relationship between animal protein intake and hemoglobin levels (p < 0.05). Conclusion: There is a significant relationship between animal protein intake and hemoglobin levels in adolescent girls. Suggestion: Education on balanced nutrition is important to increase awareness and improve eating habits in adolescents to prevent anemia. Keywords: Adolescent Girls; Anemia; Animal Protein; Hemoglobin. Pendahuluan: Anemia merupakan salah satu masalah gizi yang umum terjadi pada remaja putri, terutama di masa pertumbuhan yang pesat. Salah satu faktor utama penyebab anemia adalah rendahnya asupan protein hewani, yang mengandung zat besi heme dan berperan penting dalam pembentukan hemoglobin. Remaja putri memiliki kebutuhan zat besi yang lebih tinggi, sehingga berisiko lebih besar mengalami anemia apabila pola makan tidak mencukupi. Tujuan: Untuk mengetahui hubungan asupan protein hewani, IMT/U, waktu tidur dengan kadar hemoglobin pada remaja putri di SMA. Metode: Penelitiian menggunakan pendekatan kuantitatif dengan desain cross sectional. Subjek penelitian berjumlah 87 remaja putri kelas X dan XI yang dipilih menggunakan teknik total sampling. Data asupan protein hewani dikumpulkan melalui kuesioner semi kuantitatif FFQ, dan kadar hemoglobin diukur menggunakan alat digital hemoglobin meter. Data dianalisis menggunakan uji Spearman Rank dengan tingkat signifikansi 0.05. Hasil: Sebagian besar responden memiliki asupan protein hewani dalam kategori kurang (91.9%). Sebanyak 30.2% responden mengalami anemia ringan, dan 4.7% mengalami anemia sedang. Hasil uji statistik menunjukkan adanya hubungan yang signifikan antara asupan protein hewani dengan kadar hemoglobin (p < 0.05). Simpulan: Terdapat hubungan yang signifikan antara asupan protein hewani dengan kadar hemoglobin pada remaja putri. Saran: Pentingnya edukasi gizi seimbang untuk meningkatkan kesadaran dan pola makan remaja dalam mencegah anemia. Kata Kunci: Anemia; Hemoglobin; Protein Hewani; Remaja Putri.